Relationship between Progressive Cup Disc Ratio and Intraocular Pressure in Primary Open Angle Glaucoma After 2 Antiglaucoma Agents for 3 Months - M Fadhil Syafridon; Fidalia; Prima Maya Sari (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Primary open-angle glaucoma (POAG) is a subset of glaucoma defined by an open, normal-appearing anterior chamber angle and raised intraocular pressure (IOP) with no other underlying disease. Globally 57.5 million people were affected by primary open-angle glaucoma (POAG) in 2015, rising to 65.5 million by 2020. POAG can further lead to optic nerve damage, which can cause total blindness. POAG cannot be cured but can be controlled with medical therapy, laser, and surgical procedures. Antiglaucoma drugs are a method of treatment that can overcome this disease. This study aims to determine the characteristics of patients with POAG and progressivity of cup to disc ratio and intraocular pressure after 3 months of management of 2 antiglaucoma agents in POAG patients in Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study retrospectively reviewed the medical records specific to primary open-angle glaucoma. Data was obtained from the patient register book recorded from February 2022 to May 2022 in Dr. Mohammad Hoesin General Hospital Palembang. The parameters analyzed were patients' profiles, namely gender, intraocular pressure, and cup to disc ratio before and after 3 months of combination 2 antiglaucoma agents. Timolol and latanoprost are the 2 antiglaucoma agents given to patients diagnosed of previous POAG (by an ophthalmologist). Results: From 30 patients diagnosed with POAG by an ophthalmologist, the number of primary open-angle glaucoma patients was more female, namely 19 patients (63.3%) than 11 male patients (36.7%), with a ratio of 1.28:1 between women and men. The cup to disc ratio between before and after 3 months of therapy using timolol and latanoprost was 0.628 ± 0.04 before therapy to 0.645 ± 0.06 after therapy (p<0.05). Intraocular pressure before and after 3 months of therapy was 24.76 ± 2.63 before therapy to 17.75 ± 2.08 (p<0,05). Both cup to disc ratio and intraocular pressure differs statistically from before and after therapy. Conclusion: Fixed combination therapy of timolol and latanoprost is effective in lowering intraocular pressure and reducing cup to disc ratio progressivity in patients with primary open-angle glaucoma.